Contratações sustentáveis na administração pública brasileira: a experiência no Poder Executivo Federal Fortaleza, Ceará - Alencastro, Maria Alice Cruz (2014)
The use of natural resources has always been an essential element in the development and reproduction of human life. The increase in discussion regarding the consumption patterns of industrial societies and subsequent environmental impacts has led to the perception of the State as a significant consumer of goods and services. In response, various countries have adopted and passed guidelines and methodologies, including sustainability criteria, within their procurement practices, a practice that became known as sustainable public procurement (SPP). This study analyzes the implementation of SPP within the Brazilian Federal Executive Power. Probability sampling was used to achieve the established goals of the analysis. 24 ministries were considered as populations from which a sample of 12 ministries was obtained using a confidence level of 95% and a percent error level of 3. The procurement practices from 2010 to 2013 of the sampled agencies were analyzed. An analysis of the implementation practices used by SPP of the Federal Executive Power was realized observing the stages of the PDCA cycle. Primary data was collected from representatives of each agency through verbally administered structured questionnaires. The research demonstrated that the instruments developed for the implementation of SPP practices emphasize the mitigation of environmental impact at the expense of social aspects. Taking into account the legal and institutional instruments created by the Federal Executive Power since 2010, it was concluded that the SPP policy utilized by the Brazilian Federal Executive Power has a solid basis. However, the research highlights the underuse of these tools, particularly by sample agencies. The underutilized goals of SPP implementation within the Plan of Action for Sustainable Production and Consumption (PSPC) are duplicated in the Sustainable Logistics Plan (SLP), and elaborated by the sampled agencies. Limiting factors identified were the absence of clear targets and goals within the entities and agencies of the Federal Public Administration, and the lack of managerial support within the sampled populations. Furthermore, it was observed that the absence of systemized data makes it impossible to evaluate progress toward achieving the goals set by the agency, as well as evaluating the effectiveness of the Brazilian Federal Executive Power’s SSP policy.